MAGNETOHYDRODYNAMICS NANOFERRO FLUID FLOWS PASSING THROUGH A MAGNETIC POROUS SPHERE UNDER THERMAL RADIATION EFFECT - Widodo, Basuki; Pamela, Eirene Juwita Ningtyas; Adzkiya, Dieky; Imron, Chairul; Rahayuningsih, Tri (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
In the application of thermonuclear reactor cooling, temperature regulation relies on experiments based on practical experience. Therefore, the accuracy of this temperature setting is operator-dependent. So it is necessary to develop a mathematical model to solve these problems. The dimensional mathematical model therefore is generated using the conservation laws of mass, momentum, and energy. The dimensional mathematical model is further transformed into non-dimensional mathematical model by using non-dimensional variables. The non-dimensional mathematical model is simplified using the similarity equation by utilizing the stream function. The model obtained is a system of nonlinear ordinary differential equations. This system of equations is then solved using an implicit numerical method using Keller-Box scheme. This Keller-Box method has high accuracy and is more efficient. The numerical simulation results show that the velocity profile and temperature profile decrease as the magnetic parameter, porosity parameter, and the Prandtl number increases, respectively. Meanwhile, when the radiation parameter increases, the temperature profile also increases, but the radiation parameter does not affect the velocity profile.